Evidence of Plasmon Enhanced Charge Transfer in Large‐Area Hybrid Au–MoS2 Metasurface. Issue 24 (27th October 2020) - Camellini, Andrea; Mazzanti, Andrea; Mennucci, Carlo; Martella, Christian; Lamperti, Alessio; Molle, Alessandro; Buatier de Mongeot, Francesco; Della Valle, Giuseppe; Zavelani‐Rossi, Margherita
Abstract: Hybrid plasmonic‐semiconductor assemblies are receiving considerable attention due to the possibility to achieve hot‐carrier‐based photodetection. In this context, 2D transition metal dichalcogenides (TMDs) coupled to metal nanostructures are very promising. However, the plasmon‐to‐TMD carrier injection process is extremely challenging to achieve and even to reveal in a clear‐cut way. Herein, a report of multiple transient absorption ultrafast measurements, with tunable pump excitation, enabling quantitative comparison between the ultrafast behavior of metal nanostructures, TMDs, and their assembly is shown. This allows to provide the evidence of plasmon‐enhanced charge injection from Au nanostripes to a rippled‐shaped molybdenum disulfide (MoS2 ) few‐layer nanosheet. Finite element method numerical simulations and modeling of the transient optical response corroborate the charge transfer mechanism, showing that the experimental data cannot be described in terms of the thermomodulational nonlinearity of gold nanostripes or by simple superposition of metal and semiconductor responses. The sample is obtained by a self‐organization process on a large area; this demonstrates that plasmon‐enhanced photon harvesting exploiting hot‐electron injection can be achieved on a large area (approximately cm 2 ) surface and provides a substantial advancement toward scalable ultrathin photodetection devices based on hot‐electrons technology. Abstract : A hot‐electron injection process in large area (approximately cm 2 ) hybrid Au–MoS2 self‐organized metasurface is demonstrated by means of a series of pump–probe experiments supported by finite element method numerical simulations. The possibility to achieve hot‐electron injection on a large area provides a substantial advancement toward scalable hot‐electron devices employing 2D materials.